Pengaruh Biaya Operasional Terhadap Laba Bersih Pada PT. Golden Sumatera Bandar Lampung - Tito Budi Raharto (Pusat Riset dan Inovasi Nasional, 2023)
Golden Sumatra Bandar Lampung is a service company that operates in the transportation sector. The company in carrying out operational activities definitely requires costs, if there are no costs it is impossible for these activities to be carried out. Operational costs are related to company income, so operational costs are interrelated, where if income is greater than operational costs, the company will get greater profits. The population and sample in this study were 36 months. So there are results that there is an influence of operational costs on net profit at PT Golden Sumatra Bandar Lampung.